Kalker’s coefficient c11 and its influence on the damping and the retuning of a mechanical drive torsion system of a railway vehicle - Vojtěch Dybala (Acta Polytechnica CTU Proceedings)
Within the research of electromagnetically excited torsion oscillations in the mechanical part of traction drive systems of modern railway vehicles, which has been realized at the Faculty of mechanical engineering at the CTU in Prague, there are two separate simulation models in use. The basic calculation model, which is utilized to gain basic characteristics of the torsion system as natural frequencies and natural modes of oscillations. And the complex simulation model, which simulates a drive of the vehicle. This contribution is focused on the basic calculation model, which has been built in MATLAB. This model in its first version did not apply the contact between wheels and rails. It was necessary to find out, if this simplification is relevant with respect to subsequent simulations within the complex simulation model and its results. Therefore, the contact interaction as a traction force in longitudinal direction in the wheel-rail contact was realized via the Kalker’s linear theory. This article deals with the comparison between models with and without the implementation of the wheel-rail contact and its influence on the damping within the torsion system and retuning of the torsion system.